Nanoparticle Shape: The Influence of Nanoparticle Shape on Protein Corona Formation (Small 25/2020). Issue 25 (25th June 2020) - Madathiparambil Visalakshan, Rahul; González García, Laura E.; Benzigar, Mercy R.; Ghazaryan, Arthur; Simon, Johanna; Mierczynska‐Vasilev, Agnieszka; Michl, Thomas D.; Vinu, Ajayan; Mailänder, Volker; Morsbach, Svenja; Landfester, Katharina; Vasilev, Krasimir
Abstract : In article number 2000285, Katharina Landfester, Krasimir Vasilev, and co‐workers describe the role of nanoparticle shape in protein corona formation from human serum and plasma. Precisely engineered mesoporous silica nanoparticles with identical surface chemistry, but different shapes result in different protein corona compositions. Rod‐shaped particles adsorb more immunoglobulin and less albumin proteins compared to the sphere particles.